Efeito de exercício físico e estatinas no perfil lipídico e na função muscular em ratos dislipidêmicos - Accioly, Marilita Falangola (2007)
Statins are used to treat dislipidemias with great tolerance,however, several side effects can occur, specially myopathies. The regular practice of physical exercise (PE) produce beneficial alteration in the lipidic profile, however can generate muscle injuries. OBJECTIVE -To evaluate the effect of PE in the lipidic profile; the efficacy of the assocciation between PE and statins in the control of the lipidic profile and evaluate the effect of the association between PE and statins in the muscular function through histological analysis. MATERIAL/METHOD- It was used 80 male Wistar rats ,distributed in 8 groups, including animals submitted to a hypercholesterolemic diet (HD), simvastatin with (G1) and without (G2) PE; HD and fluvastatin with (G3) and without PE (G4); fed with comercial ration (CR) in presence (G5) and absence (G6) of PE; HD submitted (G7) or not to PE (G8). The HD was administered for 90 days, statins and practice of PE in the treadmill for 8 weeks. It was measured in the beginning (T0) and at the end (T2) of the experiment the level of total cholesterol (TC) , the fraction of cholesterol of high density lipoprotein (HDLc), triglycerides (TG), piruvic glutamic transaminase (TGP) and the fraction of the cholesterol non-HDLc (non-HDLc) was calculated. The animals were sacrificed, the soleus muscle removed for histological analysis. The paired t test and multivaried analysis were applied with a significance level of p<0,05. RESULTS â The analysis of the groups, at the T2, showed reduction in the TC level when compared G3 with groups G1 (p=0,0414), G6 (p=0,0021) and G8 (p=0,0099) and G7 with group G8 (p<0,0001). However, G1 presented elevated levels in relation to G5 (p=0,0286), G7 (p=0,0192) and G8 (p=0,0196), as well as the G2 in comparison to G7 (p=0,0115). The PE associated with fluvastatin (G3) or simvastatin (G1) has not induced a significant increase in the levels of HDLc, when compared to G4 and G2 (p>0,05). The CR, even with sedentarism (G6) kept the levels of HDLc elevated when compared to the groups remaining. Fluvastatin, independently of the presence of PE (G3 and G4) reduced the fraction of non-HDLc in comparison to G6 (p=0,0201; p=0,0315) and G1 (p=0,0271; p=0,0390, respectively). For the triglycerides levels G1 showed elevated values compared to G3 (p=0,0278), as well as TGP (p=0,0151). The main histological alteration found were fibers of different diameter, atrophics, in degeneration, splitting, edema, inflammatory infiltrate. These alterations were observed in 90% of the animals of G1, 80% of G2, 70% of G3, 30% of G4, 40% of G5 and 30% of G7. In G6 and G8 muscular fibers with preserved morphology were identified. CONCLUSION â PE influenciates in the reduction of TC levels even with DH, becoming the differential in the reduction of TC, non-HDLc and TG with the use of fluvastatin compared to simvastatin, whilst levels of HDLc resist to increase. Conversely, the increase in TGP levels are associated with HD and the use of statins, preferably simvastatin and PE practice. Moreover, PE seems to potentialize muscle injury induced by statins.